2015
DOI: 10.1590/s0102-86502015001000009
|View full text |Cite
|
Sign up to set email alerts
|

Bispectral index in calves anesthetized with xylazine, midazolam, ketamine, isoflurane and subjected to continuous rate infusion of lidocaine

Abstract: PURPOSE:To assess the bispectral index (BIS) and recovery in calves anesthetized with xylazine, midazolam, ketamine and isoflurane and subjected to CRI of lidocaine. METHODS:Xilazine was administered followed by ketamine and midazolam, orotracheal intubation and maintenance on isoflurane using mechanical ventilation. Lidocaine (2 mg kg -1 bolus) or saline (0.9%) was administered IV followed by a CRI (100 µg kgof lidocaine (L) or saline (C). Were recorded BIS, heart rate (HR), mean arterial pressure (MAP) and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 31 publications
0
5
1
Order By: Relevance
“…A potentially important point in relation to BIS is that the values of 50 in this study and 37 in another study (Ara ujo et al 2015) are lower than BIS values reported in dogs (Ferro 2003;Lopes et al 2008a), which could suggest that the value of BIS in calves that represents a hypnotic level comparable with surgical anesthesia may be lower than in other species.…”
Section: Discussioncontrasting
confidence: 59%
See 3 more Smart Citations
“…A potentially important point in relation to BIS is that the values of 50 in this study and 37 in another study (Ara ujo et al 2015) are lower than BIS values reported in dogs (Ferro 2003;Lopes et al 2008a), which could suggest that the value of BIS in calves that represents a hypnotic level comparable with surgical anesthesia may be lower than in other species.…”
Section: Discussioncontrasting
confidence: 59%
“…In contrast, BIS values recorded in this and another study (Ara ujo et al 2015) may not be reliable indicators of anesthetic depth in the bovine species, as the BIS monitor was developed for use in humans and the values may not extrapolate to other species. The literature regarding BIS in cattle is scarce and we were unable to find reference values.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…In our study, the findings exhibited the combination of ketamine and lidocaine to be more effective and safer for pediatric anesthesia, which was evidenced by more stable vital signs (reduced SBP, HR, and RR) of pediatric patients in response to the combination treatment with ketamine and lidocaine than ketamine treatment alone. It has been suggested that IV lidocaine could potentiate changes in HR by interacting with sodium channels and repressing cellular calcium influx, thus inducing changes in depolarization and conduction velocity in myocardial Purkinje fibers . SBP change may be observed on an arterial pressure waveform induced by changes in intrathoracic pressure resulting from controlled ventilation .…”
Section: Discussionmentioning
confidence: 99%